Avian leukosis viruses of different subgroups and types isolated after passage of Rous sarcoma virus-Rous-associated virus-0 in cells from different ring-necked pheasant embryos. - Temin, H M (1976)
Avian leukosis viruses of subgroups A and F (RAV-A and RAV-F) arose at a low rate after passage of Rous sarcoma virus-Rous-associated virus-0, which is subgroup E, in cells from ring-necked pheasant embryos. In cells of two embryos, all of the viruses isolated after virus passage were RAV-F. However, in cells of a third embryo, both RAV-A and RAV-F were isolated. In addition, there sometimes were type-specific differences among the different isolates of RAV-A and RAV-F from the cells of single embryos. These results indicate that the RAV-A and RAV-F probably arose by recombination of viral and cellular genes, that different ring-necked pheasant embryo may have different endogenous avian leukosis virus-related nucleotide sequences, and that recombination at different sites in these endogenous sequences might give rise to type-specific differences among the RAV-A and RAV-F.